Pengaruh Tingkat Penambahan Tepung Daun Singkong dalam Ransum Komersial terhadap Bobot Ampela, Jantung dan Hati Broiler Strain CP 707 - Widjaya, Nilawati (Sains Peternakan: Jurnal Penelitian Ilmu Peternakan, 2012)
The objective of the research was to determine the effect of cassava leaf meal addition in commercial diets on weight of gizzard, heart and liver of broiler strains CP 707 and find out the addition level which produced the highest weight of gizzard, heart and liver of broilers. The experiment used Completely Randomized Design with 5 dietary treatments, namely 100% commercial ration (R0), 96% commercial diet plus 4% cassava leaf meal (R1), 92% commercial diet plus 8% cassava leaf meal (R2), 88% commercial diet plus 12% cassava leaf meal (R3), 84% commercial diet plus 16% cassava leaf meal (R4). Each treatment was repeated 5 times. Variables measured were the weight of gizzard, heart and liver. Data were analyzed with ANOVA and followed by Duncan's Multiple Range Test. The addition of cassava leaf meal in commercial ration influenced weight of gizzard and heart, but did not affect liver weight. The highest weight of gizzard and heart obtained from broilers consumed 84% commercial diet with the addition of cassava leaf meal as much as 16%.